Evolution and Diversity of Hepatitis C Virus and Peculiarity of Modern Laboratory Diagnostic of Hepatitis C Markers - L. I. Nikolaeva; E. A. Leybman; G. V. Sapronov (Эпидемиология и вакцинопрофилактика)
Hepatitis C virus (HCV), which was identified in 1989 - 1990. Later it was included in new genus Hepacivirus of the family Flaviviridae. Due the genetic heterogeneity of HCV, viral isolates was decided to classificate on genotypes and sybtypes in accordance with the sequence of nucleotides in a certain area of the genome. It was discover that the virus infect only human and chimpanzee. Modern molecular epidemiological data, obtained after 2000, indicate monocentric origin of HCV from Africa, most likely from the central part. Probably, in Africa the conditions for feeling HCV-like virus from unknown non-primate mammal to human were formed. Recently HCV-like viruses were found in dogs, horses, bars, and rodents. The most common hypothesis of the HCV origin base on unknown virus, which is belong to genus Hepacivirus and does not infect human-like primate. The virus is included into group of nonprimate hepacivirus (NPHV). In last centure in our country viral intergenotype recombinant RF_2k/1b was appeared. In modern time HCV diversity can appeared as serology poor displayed forms of the virus. Drug-resistant variants of HCV can accumulate and disseminate again the background of antiviral therapy.